2018
DOI: 10.1002/msc.1247
|View full text |Cite
|
Sign up to set email alerts
|

Are measures of pain sensitivity associated with pain and disability at 12‐month follow up in chronic neck pain?

Abstract: Neither clinical nor quantitative measures of pain sensitivity were meaningfully associated with long-term patient-reported outcomes in people with chronic neck pain, limiting their clinical application in evaluating prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…From the regression model, the DASH score showed statistically significant differences between the groups in that the neuropathic group demonstrated impaired upper limb function (P = 0.002). More important, the DASH score mean of 35 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) in the nonneuropathic group versus 51 (41-67) in the neuropathic group met the minimum clinical important difference in change scores, indicating that these groups are not only statistically but also clinically different. 18 Due to the heavily skewed distribution of pain scores, the 11-point NPRS was analyzed based on percentages of those experiencing pain (NPRS 1 or higher) versus no pain.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…From the regression model, the DASH score showed statistically significant differences between the groups in that the neuropathic group demonstrated impaired upper limb function (P = 0.002). More important, the DASH score mean of 35 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) in the nonneuropathic group versus 51 (41-67) in the neuropathic group met the minimum clinical important difference in change scores, indicating that these groups are not only statistically but also clinically different. 18 Due to the heavily skewed distribution of pain scores, the 11-point NPRS was analyzed based on percentages of those experiencing pain (NPRS 1 or higher) versus no pain.…”
Section: Resultsmentioning
confidence: 98%
“…[31][32][33] This often results in poorer prognosis, and studies have identified higher levels of depression and disability. 34,35 Pain catastrophizing and pain acceptance are important in treatment outcomes, and a multidisciplinary focus has been suggested for this population. 36 Large individual variability exists in the location and intensity of neuropathic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors are important to assess the prognosis of pain conditions. Various clinical predictors of pain persistency in patients with neck and neck-arm pain have been reported [14,27,[44][45][46][47][48][49][50]. These include psychological and cognitive-behavioural factors such as posttraumatic stress and pain catastrophizing in patients with whiplash and subacute neck pain [48], an initial high level of self-reported pain and disability [45,49], older age and a history of other musculoskeletal disorders in nonspecific neck-arm pain [45,49,51].…”
Section: Introductionmentioning
confidence: 99%
“…QST parameters, such as cold hyperalgesia, was a significant predictor of poor outcome at long-term follow up in patients with whiplash [14] and dynamic QST (wind up ratio and cognitive pain modulation) in chronic pain conditions (fibromyalgia, nonspecific chronic back pain, chronic widespread pain) [27]. One single study, assessing patients with chronic neck and neck-arm pain with QST (CPT, PPT), clinical tests (neurodynamic tests), psychosocial factors (PCS, DASS-21), functional questionnaires (NDI) and neuropathic screening tools (SLANSS), demonstrated that baseline neck disability, comorbidities and higher psychological distress contributed to predicting disability at 12 months [44]. To date, this is the only study that has collected quantitative sensory and clinical tests to investigate potential predictors of chronic neck pain [44].…”
Section: Introductionmentioning
confidence: 99%
“…Predictors are important to assess the prognosis of pain conditions. Various clinical predictors of pain persistency in patients with neck and neck-arm pain have been reported [14,27,[44][45][46][47][48][49][50]. These include psychological and cognitive-behavioural factors such as posttraumatic stress and pain catastrophizing in patients with whiplash and subacute neck pain [48], an initial high level of self-reported pain and disability [45,49], older age and a history of other musculoskeletal disorders in nonspecific neck-arm pain [45,49,51].…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%